Effective Practices and Recommendations for Drive-Through Clinic Points of Dispensing: A Systematic Review. (1st June 2021) - Buck, Brian Holt; Cowan, Logan; Smith, Lisa; Duncan, Emily; Bazemore, Jodi; Schwind, Jessica S.
ABSTRACT: Objective: Drive-through clinics (DTCs) are a novel type of point of dispensing where participants drive to a designated location and receive prophylaxis while remaining inside their vehicle. The objective of this review was to identify effective practices and recommendations for implementing DTCs for mass prophylaxis dispensing during emergency events. Methods: A systematic review was conducted for articles covering DTCs published between 1990 and 2019. Inclusion criteria were peer-reviewed, written in English, and addressed DTCs sufficiently. Effective practices and recommendations identified in the literature were presented by theme. Results: A total of 13 articles met inclusion criteria. The themes identified were (1) optimal DTC design and planning via decision support systems and decision support tools; (2) clinic layouts, locations, and design aspects; (3) staffing, training, and DTC communication; (4) throughput time; (5) community outreach methods; (6) DTC equipment; (7) infection prevention and personal protective equipment; and (8) adverse events prevention and traffic management. Conclusions: DTCs are an essential component of emergency preparedness and must be optimally designed and implemented to successfully dispense mass prophylaxis to a community within 48 hours. The effective practices and recommendations presented can be used for the development, implementation, and improvement of DTCs for their target populations.